An approach to estimating gross efficiency during high-intensity exercise - de Koning, J. J.; Noordhof, D. A.; Uitslag, T. P.; Galiart, R. E.; Dodge, C.; Foster, C. (International Journal of Sports Physiology and Performance, 2013)
Purpose: Gross efficiency (GE) is coupling power production to propulsion and is an important performance-determining factor in endurance sports. Measuring GE normally requires measuring VO2 during submaximal exercise. In this study a method is proposed to estimating GE during high-intensity exercise. Methods: Nineteen subjects completed a maximal incremental test and 2 GE tests (1 experimental and 1 control test). The GE test consisted of 10 min cycling at 50% peak power output (PPO), 2 min at 25 W, followed by 4 min 100% PPO, 1 min at 25 W, and another 10 min at 50% PPO. GE was determined for the 50%-PPO sections and was, for the second 50%-PPO section, back-extrapolated, using linear regression, to the end of the 100%-PPO bout. Results: Back-extrapolation of the GE data resulted in a calculated GE of 15.8% ± 1.7% at the end of the 100%-PPO bout, in contrast to 18.3% ± 1.3% during the final 2 min of the first 10-min 50%-PPO bout. Conclusion: Back-extrapolation seems valuable in providing more insight in GE during high-intensity exercise.